Implementación de estrategias de desarrollo de mercado y de revenue management en el hotel Best Western Los Andes de América - Galvez Vallenas, Cesar (2021)
This Project show the implementation and development of revenue management and market development strategies that Best Western Los Andes de America hotel, located in Cusco, has made during the years 2011 – 2015, in order to improve its occupation and income levels, which has been affected as a consequence of the 2008 financial crisis and the AH1N1 epidemic, which affected the world and national tourism and hotel industry; and to which has added the floods that occurred in Cusco in 2010. In order to reach the recovery of the hotel, it has been implemented market development strategies aimed to online travel agencies (OTAs) and aimed to emergent markets like Brazil, Chile, Argentina, Colombia and México; and to new market segments like nature, DINKYS, LOHAS and Elderly. It also has been implemented revenue management strategies, so the market has been segmented by different distribution channels, it has been implemented a flexible pricing strategy and demand management, based in price discrimination and dynamic rates. The outcome of these strategies were positive, the hotel was able to recover from the crisis and improve its occupation, as well as increase its sales to online travel agencies, improve its average daily rate; and therefor increase its income.